Denervation of the Eustachian Tube and Hearing Loss Following Trigeminal Schwannoma Resection - Christopher J. Ito; Alexander K. Malone; Ricky H. Wong; Harry R. van Loveren; K. Paul Boyev (Journal of Neurological Surgery Reports, 2016)
Abstract